Moringa Reduces Glucose Levels and Alters Wolbachia Abundance in Drosophila melanogaster - Michaela Schaffer; D’Andre Grant; Katherine Berge; Nana Yaw Darko Ankrah (Microbiology Research, 2024)
Moringa oleifera Lam. (moringa) is a plant native to India, used as a nutritional and medicinal supplement in many cultures around the world. Moringa has been linked to maintaining metabolic homeostasis and is often marketed as a weight loss supplement and a potential remedy for diseases such as diabetes. Here, we investigate how moringa, a ‘superfood’ with predicted protective effects against chronic diseases such as diabetes, influences the nutritional physiology and microbiome composition of the fruit fly Drosophila melanogaster. We administered moringa as a dietary supplement to Drosophila, and quantified key nutritional indices: glucose, triacylglyceride, and protein levels, and fly weight. We showed that dietary moringa supplementation significantly reduced fly glucose levels by up to ~30% and resulted in substantial restructuring of Drosophila microbiota composition, altering both gut and intracellular bacterial populations. The effect of moringa on fly glucose levels is specific because other nutritional indices, namely, triacylglyceride and protein levels and fly weight, were not significantly affected by dietary moringa supplementation. This study highlights the importance of moringa as a modulator of host glucose metabolism.